Development of a stable diode laser system for cavity-assisted matter-wave interferometry - Beli Silva, Camila (2020)
The project is part of an experiment that has been developed to probe the dynamics of ultracold strontium atoms in a vertical one-dimensional optical lattice sustained by a ring cavity. A fundamental part of the experiment is the achievement of a laser system with high-frequency stability and narrow linewidth. This dissertation explores the control of the phase and frequency of the radiation emitted by diode laser, which are essential devices of most atomic physics experiments. Phase and frequency control is achieved by electronic feedback systems, such as the Pound-Drever-Hall technique (PDH), optical phase-locked loops (OPLL) and injection locking. The basic principles and application of these locking methods are presented.